Diseases of tropical pasture plants - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Disease of tropical pasture plants edited by J Lenné and P Trutmann ISBN 085 198 917 9 416pp UKL60.00 CAB lnternational Wallingford, Oxon OX10 8DE, UK